Thermal Bridging and its Mitigation in Bamboo Panel Construction with Steel Frameworks and Mineral Wool Insulation - Haidong Li; Wenjun Zhang; Yunxing Zhang; Feifei Zhai; Fuming Chen (BioResources, 2023)
An energy-efficient and environmentally conscious bamboo-constructed residential structure was created, comprising bamboo composite panels, steel framework, and mineral wool insulation. To ascertain the efficacy of this particular type of wall in enhancing thermal capabilities, the finite element method was employed to analyze the factors influencing the thermal performance of the exterior wall panels, insulation layer, framework, and interior wall panels. A more judicious design and implementation strategy, known as the 3# and 8# combination scheme, was evaluated in practical applications to assess the thermal efficiency of the wall system. The findings indicated that augmenting the thickness of the inner and outer wall panels and insulation layer, reducing the framework thickness, and incorporating wooden framework as a substitute for steel framework within a certain range enhanced the thermal capabilities of bamboo-constructed walls and mitigated the adverse effects of thermal bridges. The thermal performance of the residences employing the newly developed bamboo-constructed walls surpassed that of conventional iron container houses, thereby warranting broader adoption and application in practical projects. These outcomes offer valuable insights for the optimized design of thermal performance in bamboo-constructed walls.